Hakekat Seksualitas Manusia : Perspektif Gereja Kristen Nazarene di Abad 21 terhadap Praktek LGBT - Bakhoh Jatmiko (SANCTUM DOMINE: JURNAL TEOLOGI, 2016)
Civilization and social structure have dramatically changed in these last several decades. Exponential development of globalization and the growth of technology of communication have transformed values, views and cultures of human civilization nowadays. These are the symptoms of world web wide era; where the local issues can be global discussion in minutes. In one hand, the Church of God should be sensitive to the age changes, does some adaptations and changes to be relevant. In the other hand, the Church of God should not be conformed to this world. Church of the Nazarene as one of the Christian Church denominations in the world is demanded to take the stance to deal with the changes that are happened today especially in LGBT (Lesbian, Gay, Bisexual and Transgender) issue.